1871 Tenn. Pub. Stat. 108, Elections, 1869-70 ch. 22, § 2 - (:unkn) unknown (General Publisher, 1858)
Prohibited for any person from carrying, concealed or openly, any pistol, dirk, Bowie knife, Arkansas Toothpick, or other deadly or dangerous weapon at an election, fair, race course, or other public assembly.
--
Keywords: SENSITIVE PLACES